Intellectual capital mediates good corporate governance and internal audit on the quality of financial reports PT. Akebono Brake Astra, Indonesia - Marjuki; Munawaroh; Subagja, Iwan Kurniawan (Journal of Accounting, Business and Finance Research, 2024)
This study aims to determine and analyze the influence of good corporate governance, internal audit on the quality of financial reports directly and indirectly through intellectual capital. The research was conducted at PT. Akebono Brake Astra Indonesia, with a sample size of 60 respondents. The method used in the sampling process is random sampling. The analysis model uses path analysis and descriptive analysis. The study’s findings indicate that: 1) good corporate governance has a positive and significant impact on intellectual capital; 2) internal audit has a positive and significant impact on intellectual capital; 3) good corporate governance has a positive and significant impact on the quality of financial reports; 4) internal audit has a positive and significant impact on the quality of financial reports; 5) intellectual capital has a positive and significant impact on report quality; 6) there is no positive and significant impact of good corporate governance on report quality through intellectual capital; and 7) there is not a positive and significant influence of internal audit on report quality through intellectual capital. The company’s management adheres to the principle of prudence and compliance with the articles of association and company regulations, thus fulfilling social responsibility through a commitment to community welfare and environmental sustainability, especially around the company. The company presents financial report information that can be compared with other reporting entities and with previous financial reports, thus facilitating internal and external comparisons.